Assessing sugarcane farmers’ intentions towards World Trade Organisation-driven sugar sector policy reforms in Thailand - Savita Tangwongkit; Chittur S. Srinivasan; Philip J. Jones (Heliyon, 2025)
Given the importance of the sugarcane sector, reforms could significantly affect the structure and economy of Thai agriculture. This study evaluates the intended responses of Thai sugarcane farmers to a set of policy reforms informed by the 2016 World Trade Organization (WTO) dispute, which requires the liberalisation of Thailand's sugar sector. A mixed-methods approach, beginning with stakeholder consultations, was used to design three policy scenarios: (1) government proposal (2016 government reform proposals), (2) protectionism (higher support), and (3) libertarian (lower support). A survey of 462 farmers stratified by region and farm size was conducted to assess their intention to continue or exit sugarcane farming under each scenario. The results indicated that reforms, particularly under the libertarian scenario, could significantly reduce the number of sugarcane farmers and production areas. Approximately half (48.7 %) of the respondents indicated an intention to exit under this scenario, compared to 32.3 % under the government proposal and 22 % under protectionism. Farmers' decisions were generally binary, either maintaining the status quo or exiting entirely, with exits increasing as the support cuts deepened. Responses varied by farm size and specialisation level, with small, less-specialised farms being the most vulnerable under the government proposal and protectionism scenarios. Conversely, medium-sized farms were the most adversely impacted under the libertarian scenario (56.5 % indicating exit). Probit regression identified additional determinants of exit intentions, including sex, farming experience, region, harvesting and transportation methods, and the presence of a family successor and farm advisor. These findings provide crucial insights for policymakers aiming to balance WTO compliance with the sustainability of Thailand's sugarcane sector. This is the first study to incorporate stakeholder-designed policy scenarios, offering a realistic projection of farmers' responses to hypothetical, WTO-compliant reforms.